2016
DOI: 10.5604/12321966.1219180
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of canine <i>Leishmania infantum</i> and <i>Toxoplasma gondii</i> infections in Shanghai, China, and analysis of risk factors

Abstract: The aim of this study was to determine the seroprevalence of Leishmania infantum and Toxoplasma gondii among household dogs in Shanghai (the most important industrial and commercial city in China), and to assess the possible risk factors associated with the infection. During 2014-2015, a total of 408 sera were collected from healthy household dogs and tested for L. infantum and T. gondii infection using commercial ELISA kits. The endemic characteristics according to gender, age group and breed were revealed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A previous study found that, of 1,093 confirmed cases of visceral leishmaniasis in China, only eight cases were identified by microscopic examination (Fu et al, 2013 ). In order to avoid the high incidence of false negatives by microscopic examination due to a lack of personnel, many clinical laboratories in China diagnose leishmaniasis by detection of Leishmania antibodies or antigens (Gao et al, 2015 ; Jiang et al, 2016 ). In recent years, the detection of Leishmania -specific genes by polymerase chain reaction has been carried out in clinical laboratories (Zhao et al, 2015 ), but its use is far from universal.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that, of 1,093 confirmed cases of visceral leishmaniasis in China, only eight cases were identified by microscopic examination (Fu et al, 2013 ). In order to avoid the high incidence of false negatives by microscopic examination due to a lack of personnel, many clinical laboratories in China diagnose leishmaniasis by detection of Leishmania antibodies or antigens (Gao et al, 2015 ; Jiang et al, 2016 ). In recent years, the detection of Leishmania -specific genes by polymerase chain reaction has been carried out in clinical laboratories (Zhao et al, 2015 ), but its use is far from universal.…”
Section: Discussionmentioning
confidence: 99%
“…For CanL management in China, treatment of L. infantum -infected dogs and control of vectors are instituted [ 237 ]. In Shanghai, China, dog owners have been given a sulfa drug by governmental authorities for T. gondii control since 2002 [ 237 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…For CanL management in China, treatment of L. infantum -infected dogs and control of vectors are instituted [ 237 ]. In Shanghai, China, dog owners have been given a sulfa drug by governmental authorities for T. gondii control since 2002 [ 237 ]. In Brazil, prevention methods for CanL include ectoparasiticides, vaccines, and dog culling, which has ethical controversy [ 229 , 238 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%